Examining the effects of gradual catastrophes on capital modelling and the solvency of insurers: the case of COVID-19 - Muhsin Tamturk; Dominic Cortis; Mark Farrell (Risks, 2020)
This paper models the gradual elements of catastrophic events on non-life insurance capital with a particular focus on the impact of pandemics, such as COVID-19. A combination of actuarial and epidemiological models are handled by the Markovian probabilistic approach, with Feynman's path calculation and Dirac notations, in order to observe how a pandemic risk may affect an insurer via reduced business. We also examine how the effects of a pandemic can be taken into account both during and at the end of the process. Examples are also provided showing the potential effects of a pandemic on different types of insurance product.
Keywords: 330; risk theory; catastrophe risk modelling; COVID-19; dependence; pandemic